Keabsahan Alat Bukti Digital dalam Pembuktian Kasus Phantom Hacker Scam - Tegar San Putra; Sigit Sapto Nugroho; Meirza Aulia Chairani (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines the validity of digital evidence in proving cases of phantom hacker scams, a form of cybercrime committed by manipulating digital identities and false electronic footprints to deceive victims. The object of this study is digital evidence used in law enforcement against information technology-based fraud. The purpose of this study is to analyze the legal regulations related to digital evidence and assess its evidentiary strength in uncovering and proving cases of phantom hacker fraud. The research method used is normative legal research with a regulatory and contextual approach, through an examination of provisions of criminal law, criminal procedure law and the Information and Electronic Transactions Law. The results show that digital evidence has legal validity as long as it is obtained and managed in accordance with the principles of legality, integrity, and authentication as stipulated in the legislation. However, proving cases of phantom hacker scams faces technical and legal challenges, particularly regarding the validity of digital forensics and the linkage of evidence to the perpetrator. Therefore, strengthening law enforcement capacity and digital evidence standards are important factors in ensuring the effectiveness of cybercrime law enforcement.